The Influence of Entrepreneurial Knowledge on Entrepreneurial Interest in the Fashion Sector in Phase F Students of the Fashion Design and Production Program of SMKN 2 Lamongan - Aziza, Mar'atul; Yuniati, Mita; Hidayati, Lutfiyah; Arifiana, Deny (Journal of Education Method and Learning Strategy, 2025)
This study aims to: 1) Describe the level of entrepreneurial knowledge of students, 2) Describe the level of entrepreneurial interest of students, 3) Describe the influence of entrepreneurial knowledge on students' entrepreneurial interest. This study is quantitative research with an expost facto design. The population in the study is all students of the fashion design and production expertise program at SMKN 2 Lamongan. The sampling technique used was purposive sampling with a sample of 51 students. Data collection techniques are in the form of documentation and questionnaires. The data analysis technique uses simple linear regression analysis. The study results showed that 1) Students' knowledge level reached the highest level of 50% in the range of 90-100 scores, and students were declared complete. 2) The entrepreneurial interest of students in the very good category reaches 40.4%. Still, the entrepreneurial interest of students in the low and low category is also quite large, namely 40% with 22 students. 3) Entrepreneurial knowledge had no effect on entrepreneurial interest with a significance of 0.299>0.05 and a determination value (R2) of 0.22% and 99.78% influenced by other factors.